Two characterizations of consistency - Peter A. Streufert (The University of Western Ontario, Department of Economics, 2005)
This paper offers two characterizations of the Kreps-Wilson concept of consistent beliefs. One is primarily of applied interest: beliefs are consistent iff they can be constructed by multiplying together vectors of monomials which induce the strategies. The other is primarily of conceptual interest: beliefs are consistent iff they can be induced by a product dispersion whose marginal dispersions induce the strategies (a dispersion is defined as a relative probability system, and a product dispersion is defined as a joint dispersion whose marginal dispersions are independent). Both these characterizations are derived with linear algebra.
Keywords: 330